2019
DOI: 10.1136/rapm-2019-100672
|View full text |Cite
|
Sign up to set email alerts
|

Success of bedside ultrasound to identify puncture site for spinal anesthesia in neonates and infants

Abstract: Spinal anesthesia (SA) may be difficult in small infants. Conceptual advantages of ultrasound imaging to view critical neuraxial structures and exploiting the acoustic window unique to infants have been described but not clinically verified. We present 14 preterm-infants aged 35–48 weeks, weighing 1575–5800 g, and describe ultrasound imaging to locate an appropriate puncture site for SA. The success rate for first puncture was 64%, and the overall success on three attempts was 86%. The mean dural depth was 8 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
5
0
8
Order By: Relevance
“…As described previously (11), access to the subarachnoid and epidural space between C1 and C2 is easily observed. Ultrasound has also been shown to improve delivery of spinal analgesia/anesthesia in humans (17,18) where imaging helps with both reducing the number of attempts to access the SAS and time of the procedure and patient comfort (19). Further, ultrasound has been shown to minimize repeated trauma and CSF contamination in horses when used for lumbosacral CSF collection, highlighting its utility in such procedures (20).…”
Section: Discussionmentioning
confidence: 99%
“…As described previously (11), access to the subarachnoid and epidural space between C1 and C2 is easily observed. Ultrasound has also been shown to improve delivery of spinal analgesia/anesthesia in humans (17,18) where imaging helps with both reducing the number of attempts to access the SAS and time of the procedure and patient comfort (19). Further, ultrasound has been shown to minimize repeated trauma and CSF contamination in horses when used for lumbosacral CSF collection, highlighting its utility in such procedures (20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous case series on diagnostic lumbar punctures and spinal anesthetics in infants document comparatively high rates of traumatic or unsuccessful procedures; the latter is known as a “dry tap.” 1 Several studies have reported a first pass success rate of only around 60% 2 . The thecal sac in quite narrow in‐term and preterm newborns.…”
Section: Figurementioning
confidence: 99%
“…1 Several studies have reported a first pass success rate of only around 60% . 2 The thecal sac in quite narrow in-term and preterm newborns. The average lumbar anterior-posterior diameter has been estimated as approximately 4.4 mm in-term newborns.…”
mentioning
confidence: 99%
“…Durante la revisión de la literatura, se encontraron 4 estudios observacionales (14)(15)(16)(17) (Tabla 2), 7 ensayos clínicos (18)(19)(20)(21)(22)(23)(24) (Tabla 3) y 3 revisiones sistemáticas (25)(26)(27) (Tabla 4). Respecto al volumen y la calidad de la evidencia, se encontró que esta es heterogénea, asimétrica y limitada.…”
Section: Evidencia Disponible Sobre El Rendimiento De La Ecografía En...unclassified
“…En la actualidad, a pesar de que hay un consenso sobre algunas recomendaciones específicas (2) (Tabla 1), la difusión de esta técnica en los centros hospitalarios de mediana o baja complejidad es casi nula y el entrenamiento es insuficiente (11)(12)(13) . Los ensayos clínicos disponibles son antiguos y los estudios actuales solo se enfocan en condiciones específicas, por lo tanto, la evidencia es heterogenia, de distribución asimétrica, con resultados limitados (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . En función de lo anteriormente mencionado, y conociendo la relevancia de la punción en la práctica asistencial, el objetivo de este manuscrito consiste en revisar evidencia notable y reciente sobre el rendimiento de esta técnica, guiada por ecografía.…”
Section: Introductionunclassified